Deconstructing tourism in Berlin in 2000s-2010s : Urban trends, tourist identities and local transformation - Kuznetsova, Valeria (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis aims to deconstruct the case of anti-tourism discourse in Berlin in 2000s-2010s. The purpose of the study is to analyze connection of place, lifestyle, and identity with tourism. A selection of online articles and posts was carefully studied. The most important themes were discerned and examined in the context of related academic research. Tourism, authenticity, and urban development are the core themes of the analysis. Anti-tourism discourse in Berlin reveals complex interconnection of issues such as traveling, identity, and tourism effects. Study of anti-tourism discourse in Berlin illustrates the ambiguity of tourism. The thesis demonstrates that tourism develops into the variety of trends, and its effects are conflicting with the interests of residents. Local lifestyle is associated with the alternative vibe and creative spirit and plays a massive role in constructing Berlin’s attraction. At the same time, tourism in Berlin is concentrated in the residential areas. Tourism activity is defined by the high level of intrusion into ordinary local life and leads to such consequences as gentrification. Tourism in Berlin reflects the global trends in work and leisure. At the same time, general development, real estate market, and local culture are the factors that make Berlin different. Achieving city’s sustainable development requires balancing tourism growth with urban development and careful consideration of the variety of issues that shape Berlin.